Reconfigurable 2, 3 and 5-point DFT processing element for SDF FFT architecture using fast cyclic convolution algorithm - S, Bibin Sam Paul; Glittas, A.X; Sellathurai, M; Lakshminarayanan, G (Electronics letters, 2020)
In this Letter, a reconfigurable processing element (PE) for pipelined SDF FFT architecture is presented, which can be configured to compute 2, 3 and 5-point DFTs. Foremost, the proposed PE architecture for the 5-point DFT computation is designed by factorising the 5-point DFT computation operation into $2× 2$2×2 cyclic convolution units and then the 2- and 3-point DFTs structures are mapped on to it using multiplexers. Thus, all three configurations are possible. In the case of prior 5-point PE designs, the PE can start its operation only after the arrival of all the five-input data, whereas the proposed PE completes a part of computation after the arrival of the first three inputs and reuse the same hardware to process the next two inputs. As a result, the proposed PE requires less hardware, at the same time, preserving the throughput of prior PE. The proposed PE required 25% less multiplier and one adder less compared to the Winograd algorithm based 5-input PE.